1990
DOI: 10.1117/12.20474
|View full text |Cite
|
Sign up to set email alerts
|

Efficient acousto-optically phase-matched noncollinear optical second-harmonic genertion in tellurium

Abstract: Two kinds of efficient acousto-optically phase-matched non collinear optical SHG are predicted in Te for the incident optical wave at lO,6p in.The first one is calculated with the shear acoustic wave propagating along the X localized by the three Euler angles cp=° , 0=1 500, 1600 , 4 450, and is interpreted as being due to mixing of the incident optical wave and the acousto-optically scattered wave. The other SHG is observed with the same slow acoustic shear wave and is due to the mixing ot the two acousto-opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The Te crystal belongs to the class of crystalline materials 32 (D 3 ) of the trigonal system [1,2,[14][15][16][17][18][19][20][21][22][23][24]. Te is transparent in the IR region from 4 to 23 µm and noticeably differs from other crystalline materials transparent in the IR [1][2][3][4][5][6][7][8][9][10].…”
Section: Optical Characteristics Of Te Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…The Te crystal belongs to the class of crystalline materials 32 (D 3 ) of the trigonal system [1,2,[14][15][16][17][18][19][20][21][22][23][24]. Te is transparent in the IR region from 4 to 23 µm and noticeably differs from other crystalline materials transparent in the IR [1][2][3][4][5][6][7][8][9][10].…”
Section: Optical Characteristics Of Te Crystalmentioning
confidence: 99%
“…For example, the indices of refraction of Te for the extraordinary and ordinary polarized light at 10.6 µm are quite large, i.e. n e = 6.25 and n o = 4.8, showing that the crystal possesses extremely strong optical anisotropy n ≡ n e − n o = 1.45 [16,[25][26][27]. The large refractive indices give rise to the high values of the Fresnel reflection coefficients for light intensity, i.e.…”
Section: Optical Characteristics Of Te Crystalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although tellurium has been known for decades, the material has not been investigated in details, especially if the imaging acousto-optic applications are taken into the consideration. For example, the extraordinary high acousto-optic figure of merit of the material seems rather doubtful [29][30][31] because only once experiments with the crystal confirmed that the figure of merit of the crystal was really high [30]. However, the high value was observed not in a filter but deflector configuration of the crystal.…”
Section: Introductionmentioning
confidence: 99%